2011
DOI: 10.1007/s11483-011-9221-4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Moisture Sorption Characteristics of Oat Flour by Static and Dynamic Techniques with and Without Thymol as an Antimicrobial Agent

Abstract: The effectiveness of thymol as an antimicrobial agent during the determination of equilibrium moisture sorption data at high-water activities (0.50-0.98) was studied at 5, 23, and 45°C in oat flour. The static gravimetric (SG) method (with and without added thymol) and the dynamic vapor sorption technique (DVS) were used. Microbial growth in samples conditioned in these environments at temperatures of 5 and 45°C was null indicating no need for the use of thymol at these temperatures. However, samples confined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
1
5
0
1
Order By: Relevance
“…For instance, León‐Martínez et al () also observed Type III behavior for components rich in sugar and carbohydrates in cactus mucilage. Starch‐rich products also have similar sigmoidal behavior to that one obtained in this study, as presented by Oyelade, Tunde‐Akintunde, Igbeka, Oke, and Raji () and Sandoval, Guilarte, Barreiro, Lucci, and Müller () for maize and oat flour, respectively; where isotherms Type II were obtained, characteristic for products with high water solubility. It is important to note that sorption behavior of spray‐dried products is a function of the wall materials used for microencapsulation (Beristain, Azuara, & Vernon‐Carter, ).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…For instance, León‐Martínez et al () also observed Type III behavior for components rich in sugar and carbohydrates in cactus mucilage. Starch‐rich products also have similar sigmoidal behavior to that one obtained in this study, as presented by Oyelade, Tunde‐Akintunde, Igbeka, Oke, and Raji () and Sandoval, Guilarte, Barreiro, Lucci, and Müller () for maize and oat flour, respectively; where isotherms Type II were obtained, characteristic for products with high water solubility. It is important to note that sorption behavior of spray‐dried products is a function of the wall materials used for microencapsulation (Beristain, Azuara, & Vernon‐Carter, ).…”
Section: Resultssupporting
confidence: 85%
“…The initial moisture content of the microencapsulated juice after spray drying was 2.26 AE 0.005% (g water/100 g dry basis). Figure 1 (2008) and Sandoval, Guilarte, Barreiro, Lucci, and Müller (2011) for maize and oat flour, respectively; where isotherms Type II were obtained, characteristic for products with high water solubility. It is important to note that sorption behavior of spray-dried products is a function of the wall materials used for microencapsulation (Beristain, Azuara, & Vernon-Carter, 2002).…”
Section: Water Sorption Isothermsmentioning
confidence: 95%
See 1 more Smart Citation
“…It is noteworthy that these compounds have been widely used in fields for such use as flavor additives and pharmaceuticals for human consumption. For example, 2-nonanone is naturally produced in volatiles which are released by red raspberries and strawberries (Vaughn et al, 1993) and thymol has been used in oat flour as an antimicrobial agent (Sandoval et al, 2011). As a result of the widespread use of these volatiles in the food industry, they have come to be considered a safe alternative to control mango anthracnose disease.…”
Section: Discussionmentioning
confidence: 99%
“…The following salts and the corresponding water activities at 25 °C in parenthesis were used [13]: KOH (0.082), LiCl (0.113), KCH 3 CO 2 (0.225), MgCl 2 (0.328), K 2 CO 3 (0.432), Mg(NO 3 ) 2 (0.529), CoCl 2 (0.649), NaCl (0.753), (NH 4 ) 2 SO 4 (0.810), KNO 3 (0.936) and K 2 SO 4 (0.973). Thymol was used as antifungal agent in the desiccators with ambient with relative humidity above 81% to avoid alterations by mold growth that could affect the results of the experiments [14]. The static gravimetric (SG.…”
Section: Moisture Sorption Isothermsmentioning
confidence: 99%